PENGARUH DISCOVERY LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS FABEL - Azizah, Nazif Fatul; Ratna, Ellya; Hafrison, Mohammad (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT The purpose of this study was (1) to describe the skill level of writing text fable class VII students SMPN 5 Koto XI Tarusan before using the model of discovery learning media of series image, (2) to describe the skill level of writing text fable class VII students SMPN 5 Koto XI Tarusan after using the model of discovery learning media of series image, (3) to describe the effect of discovery learning model with serialized media aid to the skill of writing fable text of gride students SMPN 5 Koto XI Tarusan. This type of research is quantitative with experimental method. Based on the results of the study concluded that use of media assisted discovery learning model of series images can be used as an alternative to fable text learning. Kata kunci: discovery learning, gambar berseri, fabel